2009
DOI: 10.1002/bio.1101
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the tris(2,2′‐bipyridine) ruthenium(II)‐catalyzed Belousov–Zhabotinsky oscillating chemiluminescence reaction by l‐cysteine and its application

Abstract: Perturbation of the tris(2,2'-bipyridine)ruthenium(II) [Ru(bpy)(3)2+]-catalyzed Belousov-Zhabotinsky (BZ) oscillating chemiluminescence (CL) reaction induced by L-cysteine was observed in the closed system. It was found that the CL intensity was decreased in the presence of L-cysteine. Meanwhile, oscillation period and oscillating induction period were prolonged. The sufficient reproducible induction period was used as parameter for the analytical application of oscillating CL reaction. Under the optimum condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, Liu and Han described the perturbation of a Ru(bpy)3 2+ -catalyzed BZ oscillating CL system by L-cysteine and application of oscillating induction period for L-cysteine determination (70). Under the optimum reaction conditions established, the changes in the oscillating CL induction period were linearly proportional to the concentration of L-cysteine in the range from 8.0 ¥ 10 -7 to 5.0 ¥ 10 -5 M with a detection limit of 4.3 ¥ 10…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, Liu and Han described the perturbation of a Ru(bpy)3 2+ -catalyzed BZ oscillating CL system by L-cysteine and application of oscillating induction period for L-cysteine determination (70). Under the optimum reaction conditions established, the changes in the oscillating CL induction period were linearly proportional to the concentration of L-cysteine in the range from 8.0 ¥ 10 -7 to 5.0 ¥ 10 -5 M with a detection limit of 4.3 ¥ 10…”
Section: Applicationsmentioning
confidence: 99%
“…The most widely studied of the [Ru(bpy) 3 ] 2+ -catalyzed BZ oscillators was the reaction developed by Demas and Diemente in 1973 (12), which was based on the oxidation of KBrO 3 by malonic acid (MA) in a strongly acidic medium and was catalyzed by trace amounts of [Ru(bpy) 3 ] 2+ . This reaction took place in both closed (18,19) and open (20) systems; however, in the former oscillations gradually damped and eventually reached another equilibrium state. This reaction took place in both closed (18,19) and open (20) systems; however, in the former oscillations gradually damped and eventually reached another equilibrium state.…”
Section: Introductionmentioning
confidence: 99%
“…Later, in 1982, Bolletta et al (12) observed the first example of an oscillating CL system for the [Ru(bpy) 3 ] 2+ -catalyzed BZ reaction and reported an oscillatory CL curve with a sub-peak. This reaction took place in both closed (18,19) and open (20) systems; however, in the former oscillations gradually damped and eventually reached another equilibrium state.…”
Section: Introductionmentioning
confidence: 99%